Аналіз стану основних засобів підприємств харчової промисловості - Михайленко, Ольга Валеріївна; Бородій, Дарина Андріївна (My University, 2019)
У статті досліджено стан основних засобів на підприємствах харчової промисловості. Визначено місце основних засобів харчової промисловості у загальній вартості основних засобів усіх галузей України (згідно з КВЕД-2010). Виділено два основних відносних показника аналізу стану основних засобів, а саме коефіцієнт зносу та коефіцієнт придатності. Встановлено, що оцінювання технічного стану основних засобів має велике значення для подальшого розроблення заходів щодо оновлення основних засобів. Виявлено негативні тенденції зростання зносу основних засобів та зменшення їх придатності, проблеми щодо оновлення основних засобів на досліджуваних підприємствах. На підставі проведеного аналізу запропоновано перелік заходів щодо покращення стану основних засобів на підприємствах харчової промисловості. Зокрема, на підприємствах необхідно проводити періодичні ремонти, які допомагають усунути тимчасовий фізичний знос, а також поступово оновлювати основні засоби та амортизаційну політику. Важливо також вживати заходів щодо підвищення ефективності використання основних засобів, адже це вплине на їх стан. The article investigates the state of fixed assets at food industry enterprises. The place of fixed assets of the food industry in the total value of fixed assets of all branches of Ukraine is determined (in accordance with QWED-2010). Two main relative indicators for the analysis of the state of fixed assets are distinguished: the coefficient of wear and the coefficient of suitability. The article presents material on the dynamics of initial and residual value, as well as the depreciation of fixed assets at four food industry enterprises. It is established that the evaluation of the technical condition of fixed assets is of great importance for the further development of measures for the renewal of fixed assets. To analyze the state of fixed assets considered by the food industry enterprises of different regions and developing countries, as well as PJSC “Obolon”, LLC “Yagotin Butter Plant”, PrJSC “Myronivsky Hliboproduct”, PJSC “Kozyatinsky meat-packing plant”. For each of these enterprises, the indicators of fixed assets were determined, namely the coefficient of wear and the coefficient of suitability. The negative tendencies of depreciation of fixed assets growth and decrease of their suitability are revealed, as well as problems with the renewal of fixed assets at the enterprises under study. A significant part of the food industry enterprises have a large percentage of fixed assets depreciation, which increases the technical and technological backwardness of enterprises, which in turn affects the cost of maintaining fixed assets, labor productivity, quality of production and, ultimately, the financial result of the enterprise. On the basis of the analysis, a list of measures aimed at improving the state of fixed assets at the enterprises of the food industry is proposed. In particular, at enterprises it is necessary to carry out periodic repairs that help to eliminate temporary physical wear, as well as gradually update the fixed assets and depreciation policy. It is also important to take measures to increase the efficiency of the use of fixed assets, as it will affect their condition. One of the main tasks of the development of food companies is the interest of entrepreneurs to carry out modernization, qualitative renewal of production, due to depreciation policy.
Keywords: основні засоби; харчова промисловість; ступінь зносу; коефіцієнт придатності; структура основних засобів; ефективність використання; капітальні вкладення; fixed assets; food industry; degree of wear; coefficient of suitability; structure of fixed assets; efficiency of use; capital investments; кафедра обліку і аудиту